High-temperature mechanical performance of bagasse fiber ceramsite concrete and mortar - Yu, Xiaoping; Liu, Cunpeng; Wang, Jialiang; Liu, Maojun; Bai, Dalian; Zhou, Shengkai; Chen, Junwen; Liu, Jing (Frontiers in Materials, 2025)
Ceramsite concrete has gained prominence in sustainable construction and sponge city development owing to its lightweight nature and thermal insulation properties. However, its inherent brittleness and low tensile strength have restricted broader applications. Emerging research highlights fiber reinforcement as an effective enhancement strategy. This study innovatively integrates waste sugarcane bagasse fibers into mortar formulations, conducting comprehensive mechanical tests across varying fiber ratios. Experimental results reveal significant improvements in flexural, compressive, and split tensile strengths with fiber incorporation, with the split tensile strength exhibiting a maximum enhancement of 17.7%. Optimal mechanical performance is achieved at a fiber content of 3% by volume. This study also explores the mechanical performance of bagasse fiber ceramsite concrete (BFRLC) with different bagasse fiber content (0%–6%) at different high temperatures (25–700°C). Under thermal exposure ranging from 25°C to 700°C, the compressive and splitting tensile strength of BFRLC demonstrates an increasing trend with increasing sugarcane fiber content before decreasing, with optimal mechanical performance observed at 4.5 vol% fiber volume fraction. At 500°C, the BFRLC containing 4.5 vol% sugarcane fibers exhibited 10.0% and 39.7% improvements in compressive strength and splitting tensile strength, respectively, compared to standard ceramsite concrete. More significantly, both compressive and splitting tensile strengths of BFRLC exhibit a biphasic degradation pattern under thermal loading, demonstrating gradual deterioration followed by a precipitous decline as temperature escalates, with 500 °C representing the critical thermal transition threshold. Compared to 500°C, at 700°C, the compressive strength of BFRLC is reduced by up to 42.3%, and the split tensile strength of BFRLC is reduced by up to 59.7%. These findings provide quantitative guidelines for optimizing bagasse–ceramsite concrete formulations and processing methodologies, effectively balancing mechanical performance, thermal stability, and environmental sustainability.